2020
DOI: 10.1093/jxb/eraa532
|View full text |Cite
|
Sign up to set email alerts
|

The rice LRR-like1 protein YELLOW AND PREMATURE DWARF 1 is involved in leaf senescence induced by high light

Abstract: Senescence is induced by endogenous physiological changes or exogenous stresses in plants. Here, we isolated two alleles of a novel rice (Oryza sativa L.) mutant, yellow and premature dwarf 1 (ypd1). The ypd1 mutants exhibited a yellow and dwarf phenotype from germination, and premature senescence starting at tillering. Moreover, the ypd1 mutants were sensitive to high light, which accelerated cell death and senescence. Consistent with their yellow phenotype, the ypd1 mutants had abnormal chloroplasts and lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The pwl1 plant showed leaf withering from the seedling stage, and the symptoms became aggravated along with growth, and the leaves were basically wilted at the booting stage (Figure 1a–c). Like most premature leaf senescence mutants (Chen et al ., 2021; Leng et al ., 2017; Xu et al ., 2022a), the premature leaf senescence of pwl1 has a negative impact on its agronomic traits, with only 50% seed setting rate and a significant reduction in the plant height, tiller number, and 1000‐grain weight (Table S1). Genetic complementarity experiments proved that PWL1 could rescue the premature leaf senescence phenotype of pwl1 , including normal leaf senescence and agronomic traits (Figure 2 and Figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pwl1 plant showed leaf withering from the seedling stage, and the symptoms became aggravated along with growth, and the leaves were basically wilted at the booting stage (Figure 1a–c). Like most premature leaf senescence mutants (Chen et al ., 2021; Leng et al ., 2017; Xu et al ., 2022a), the premature leaf senescence of pwl1 has a negative impact on its agronomic traits, with only 50% seed setting rate and a significant reduction in the plant height, tiller number, and 1000‐grain weight (Table S1). Genetic complementarity experiments proved that PWL1 could rescue the premature leaf senescence phenotype of pwl1 , including normal leaf senescence and agronomic traits (Figure 2 and Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, leaf senescence is accompanied by PCD caused by hyperaccumulation of ROS, a mechanism that has been elucidated in rice premature leaf senescence mutants (Mittler, 2017). The ypd1 ( yellow and premature dwarf 1 ) mutant showed premature senescence and accelerated cell death due to higher ROS levels in the leaves (Chen et al ., 2021). The hpa1 mutant exhibited H 2 O 2 accumulation and PCD, subsequently triggering leaf senescence (Xiong et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species are also important factors in triggering early leaf senescence and PCD in plants ( Loor et al, 2010 ; Wang et al, 2013 ; Mittler, 2017 ; Chen et al, 2021 ). The oswss1 mutant exhibited remarkable increased amounts of oxidative-stress-induced toxic compound MDA, enhanced PCD ( Figures 7C–E and Supplementary Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 185 senescence-associated genes (SAGs) have been identified in rice ( Li et al, 2020 ). These genes are mainly associated with chloroplast development ( Yang Y. et al, 2016 ; Chen et al, 2021 ), chlorophyll degradation ( Kusaba et al, 2007 ; Morita et al, 2009 ; Jiang et al, 2011 ; Yamatani et al, 2013 ; Cui et al, 2021 ), hormone signal transduction ( Kong et al, 2006 ; Chen et al, 2013 ; Liang et al, 2014 ), protease transport metabolism ( Wu et al, 2016 ; Hong et al, 2018 ), and energy transport metabolism ( Huang et al, 2007 ; Qiao et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that low light intensity can reduce the total anthocyanin and total phenolic content of purple rice during the seedling stage, while also increasing the total anthocyanin and DPPH activity of purple rice during the reproductive period . Too high light intensity can also accelerate the cell death and senescence of rice and affect chloroplast development so that the plant turns yellow …”
Section: Introductionmentioning
confidence: 99%